(untitled) (Medical Forum Monthly, 2024)
Aims and Objective: To compare the anatomical and functional results of open reduction and internal fixation of supracondylar fracture of humerus in children with parallel and cross K-wire fixation and to determine the best method of fixation, preventing complications Study design: A comparative study. Place and Duration of Study: This study was conducted in Orthopaedics department, District Head Quarter Hospital Dera Ghazi Khan from March 2011 to September 2011. Materials and Methods: Forty consecutive patients from 4 to 10 years of age (mean age of 6.4 years) with Gartland type-III supracondylar fractures of humerus, received in the emergency department were included in the study. Results: In this study, patients from 4 to 10 years of age were included. Their mean age was 6.4 years. Their age distribution is shown in Graph-1. Highest numbers of patients were from 6 to 7 years of age. Those were 17 (42.5%). The mean age of the patients in which fracture was fixed by parallel Kirschner wires, was 6.2 years and the mean age of the patients in which fracture was fixed by cross Kirschner wires, was 6.6 years. Conclusion: On the basis of above mentioned findings and review of the available literature, the conclusion of this study is that cross Kirschner wires configuration is more safer and stronger mode of fixing all Gartland type-III supracondylar fracture of humerus in children.